Pembakaran ulang abu bawah batubara - Tjokorde Walmiki Samadhi; Tishi T Daulay; M Firmansyah; Tjandra Setiadi (Jurnal Teknik Kimia Indonesia, 2008)
The high carbon content of coal bottom ashes collected from several textile manufacturing plants in the Bandung area is indicative of an opportunity for energy utilization efficiency improvement by re-combustion of the bottom ashes. This research examines the technical feasibility of bottom ash utilization as a raw material for solid fuel briquette manufacturing. This paper discusses the measurement of the impact of bottom ash content on ignition time and crushing strength of the briquette. Bottom ash content is varied in the 0-50 %-weight range (binder and moisture-free basis). The ignition time of the briquette varies in the 4.4 – 9.9 minutes range. The ignition time of the briquette is proportional to its bottom ash content, due to the decrease in its volatile matter content. The crushing strength of the briquette varies in the 13.4 – 27.1 kgf/cm2 range, which is comparable to that of typical bulk sub-bituminous coals. A 10 %-weight addition of fresh coal powder to the briquette significantly increases its crushing strength, while further adition of coal powder does not significantly increase the crushing strength.Keywords : bottom ash, briquette, coal, energy efficiencyAbstrakTingginya kadar karbon dalam abu bawah batubara yang dihasilkan oleh boiler unggun tetap di sejumlah pabrik tekstil di wilayah Bandung mengisyaratkan peluang untuk meningkatkan efisiensi pembangkitan energi melalui pembakaran ulang abu bawah tersebut. Penelitian ini mengkaji kelayakan teknis pemanfaatan abu bawah sebagai bahan baku briket bahan bakar padat. Percobaan yang dilaksanakan bertujuan mengukur pengaruh kadar abu bawah dalam briket terhadap waktu penyalaan dan kekuatan mekanik produk briket. Kadar abu bawah divariasikan pada rentang 0-50 %-berat (basis bebas aditif perekat dan air). Waktu penyalaan briket berkisar pada 4,4 – 9,9 menit. Waktu penyalaan berbanding lurus dengan  kadar abu bawah  karena berkurangnya kadar zat terbang briket. Kuat remuk (crushing strength) briket berkisar pada  13,4-27,1 kgf/cm2, yang sepadan dengan kuat remuk batubara sub-bituminus bongkahan. Penambahan serbuk batubara segar sebesar 10 %-berat memberikan peningkatan kuat remuk yang signifikan, sementara penambahan lebih lanjut serbuk batubara segar tidak meningkatkan kuat remuk briket.Kata kunci : abu bawah, briket, batubara, efisiensi energi